Neuroscience Information Toolbox: An Open Source Toolbox for EEG–fMRI Multimodal Fusion Analysis - Dong, Li; Luo, Cheng; Liu, Xiaobo; Jiang, Sisi; Li, Fali; Feng, Hongshuo; Li, Jianfu; Gong, Diankun; Yao, Dezhong (Frontiers in Neuroinformatics, 2018)
Recently, scalp electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) multimodal fusion has been pursued in an effort to study human brain function and dysfunction to obtain more comprehensive information on brain activity in which the spatial and temporal resolutions are both satisfactory. However, a more flexible and easy-to-use toolbox for EEG-fMRI multimodal fusion is still lacking. In this study, we therefore developed a freely available and open-source MATLAB graphical user interface toolbox, known as the Neuroscience Information Toolbox (NIT), for EEG-fMRI multimodal fusion analysis. The NIT consists of three modules: 1) the fMRI module, which has batch fMRI preprocessing, nuisance signal removal, bandpass filtering and calculation of resting-state measures; 2) the EEG module, which includes artifact removal, extracting EEG features (event onset, power and amplitude), and marking interesting events; and 3) the fusion module, in which fMRI-informed EEG analysis and EEG-informed fMRI analysis are included. The NIT was designed to provide a convenient and easy-to-use toolbox for researchers, especially for novice users. The NIT can be downloaded for free at http://www.neuro.uestc.edu.cn/NIT.html, and detailed information, including the introduction of NIT, user’s manual and example data sets, can also be observed on this website. We hope that the NIT is a promising toolbox for exploring brain information in various EEG and fMRI studies.